Development of sorghum millet incorporated reduced calorie flavoured milk - Giri, Apurba; Ojha, Supti (Indian Journal of Dairy Science, 2025)
Sorghum millet is rich in nutrient profile including slow digestive starches, vitamins, minerals, protein, fiber that contribute to improve health outcomes like better digestion, controlled diabetes, and enhanced cardiovascular health. Stevia is a natural sweetener with zero calories and is attracted diabetics and health conscious people. This research aimed to optimize the level of sorghum and stevia in flavoured milk. In this study, the addition of millet in various batches were 1%, 2%, 3%, 4% and for the next step, the optimization of stevia level in various batches were 1%, 1.5% and 2%. Flavoured milk was optimized with 3% of millet addition and sugar was completely replaced by 1.5% stevia depending on sensory characteristics. Physico-chemical analysis was conducted to assess changes in moisture, fat, pH, titratable acidity and total soluble solids. In some cases they were changed significantly as compared to control.